Effect of Metal Ions on Pectinase Activity from Aspergillus niger on Purifying Guava Fruit - Dian Puspita Anggraini; Anna Roosdiana; Sasangka Prasetyawan; Diah Mardiana (Natural B, Journal of Health and Environmental Sciences, 2013)
Pectinase can be used on various fruit juices clarification; however, the activities can be affected by their metal ions content. The purpose of this study was to determine the type of metal ions inhibition i.e. Zn2+; Mg2+ and Ca2+ on the pectinase activity of Aspergillus niger, and its potential application in guava juice clarification. Activity assays performed at pH 5, temperature 50°C during 55minutes and each ion concentration were 2-10 mM. Galacturonic acid concentration, as the product of pectin substrate hydrolysis, used as the basis for determining its activity and analyzed by visible spectrophotometry. The results showed that the ions concentration of Zn2+ and Mg2+ more than 4 mM were inhibitor for pectinase activity while Ca2+ ion concentration was 6mM. KI values for the metal ions Zn2+; Mg2+ and Ca2+ at concentrations of 6mM were 176.99; 326.09 and 280.37 mM respectively. Pectinase from Aspergillus niger were able to reduce 18% of pectin of guava juice.